Host lipidome analysis during rhinovirus replication in HBECs identifies potential therapeutic targets - Nguyen, An; Guedán, Anabel; Mousnier, Aurelie; Swieboda, Dawid; Zhang, Qifeng; Horkai, Dorottya; Le Novere, Nicolas; Solari, Roberto; Wakelam, Michael J O (Journal of lipid research, 2018)
In patients with asthma or chronic obstructive pulmonary disease, rhinovirus (RV) infections can provoke acute worsening of disease, and limited treatment options exist. Viral replication in the host cell induces significant remodeling of intracellular membranes, but few studies have explored this mechanistically or as a therapeutic opportunity. We performed unbiased lipidomic analysis on human bronchial epithelial cells infected over a 6 h period with the RV-A1b strain of RV to determine changes in 493 distinct lipid species. Through pathway and network analysis, we identified temporal changes in the apparent activities of a number of lipid metabolizing and signaling enzymes. In particular, analysis highlighted FA synthesis and ceramide metabolism as potential anti-rhinoviral targets. To validate the importance of these enzymes in viral replication, we explored the effects of commercially available enzyme inhibitors upon RV-A1b infection and replication. Ceranib-1, D609, and C75 were the most potent inhibitors, which confirmed that FAS and ceramidase are potential inhibitory targets in rhinoviral infections. More broadly, this study demonstrates the potential of lipidomics and pathway analysis to identify novel targets to treat human disorders.